Periodic cellular automata : entropy, simulations and applications - Nor Raihan binti Mohamad Asimoni (Kulliyyah of Science, International Islamic University Malaysia, 2016)
Cellular automata have been captured the attention of researchers with its interesting behavior. This model is discussed mostly in one-dimensional array since its simple work can imitate complex behavior. Specifically, this thesis was carried out to introduce the notion of new type of cellular automata which is periodic cellular automata. Besides, it was performed to investigate the entropy, simulations and applications of periodic cellular automata using one-dimensional array and as a state. The overall findings of the study indicate that the entropy of such automata depends on the order of the components. In this thesis, we included the example of periodic cellular automata of period 2 and period 3. In addition, we provided different type cellular automata which is cellular automata and presented application in a line of road. In conclusion, some recommendations for future research have been included in the final part of this thesis.